Thermal Energy Storage and Energy Conversion Technologies - Lee, Ann (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Thermal energy storage (TES), also known as heat storage systems, is a technology that accumulates energy when production exceeds demand so that the stored energy can be used later. The stored energy can be used at the user's request for heating and cooling applications or for power generation. TES systems are commonly seen in buildings and industrial processes. On the other hand, conversion and storage, such as solar and wind energy, help to further increase the share of renewables in the energy mix. TES is becoming crucial for electricity storage in combination with solar power, whereby solar heat can be stored for electricity production when sunlight is absent. This is a Special Issue dedicated to recent advances in thermal energy storage and energy conversion technologies. All types of research approaches are compiled in this Special Issue: experimental, theoretical, computational, and their mixtures; papers are both of fundamental and applied nature, including industrial case studies.